Following Heavenly Orders: Heroic Deviance and the Denial of Responsibility in Narratives of Rescue. Issue 11 (2nd November 2022) - Fox, Nicole; Wise, Jamie D.; Nyseth Brehm, Hollie
ABSTRACT: This case study of heroic deviance focuses onHutu who did not participate in the genocidal violence in 1994 Rwanda and instead risked their lives to rescue Tutsi. Drawing from 45 in-depth interviews, we examine how these deviant heroes invoke religion to narrate their actions. We find that interviewees often neutralize their acts of rescue by attributing responsibility to God. We also theorize why those who engaged in rescue may use religion to neutralize their actions, including coping with trauma, mitigating stigma, and managing impressions. These findings have important implications for the study of deviance and for atrocity prevention policy.